Hypothermic cerebral protection for a patient undergoing aorto-carotid bypass - Bhusal, Surendra; Amatya, Ashish Govinda; Pokharel, Jeju Nath; Timala, Rabindra; Shakya, Shakti (Journal of Society of Anesthesiologists of Nepal, 2016)
We present a case of Takayasu arteritis with a history of double valve replacement undergoing aorto-carotid bypass and describe the anaesthetic management aimed at preserving cerebral function and protecting the cardiovascular system. The 17-year-old girl presented with recurrent loss of consciousness and absent bilateral radial artery pulses. She had total occlusion of the bilateral carotid arteries and cerebral blood flow was completely dependent on the vertebral artery. Partially clamping the aorta and carotid artery along with hemodynamic effects of general anaesthesia may further compromise the critical cerebral blood flow leading to cerebral injury. So we planned hypothermia for cerebral protection. Since she had to undergo re-sternotomy and with the possibility of haemorrhage during re-sternotomy; femoral artery and vein cannulation was done and cardiopulmonary bypass pump was started before sternotomy. Cooling was started effectively on cardiopulmonary bypass. Our aim was to provide cerebral protection by induced hypothermia at 25 degree Celsius and support of circulation with cardiopulmonary bypass. Aorto-left carotid artery bypass graft was placed with postoperative improvement in symptoms of the patient at one year follow up. A brief review of the perioperative anticoagulant management in such patients with prosthetic mechanical valves is also mentioned. Hence hypothermia and support of circulation with cardiopulmonary bypass can be considered in a patient with critical cerebral blood flow.